A Graphical Exposition of the Profit Maximizing Two-Part Tariff. (March 2022) - Chen, Frederick
This note presents a simple graphical approach for deriving the profit maximizing two-part tariff when there are two types of consumers in the market. The exposition covers both the case in which a monopoly can offer only one two-part tariff plan and the case in which the monopoly can offer two different plans. JEL Classification : D4